Challenges in the governance of community-managed forests in Ethiopia: review - Yami, M.; Mekuria, Wolde (MDPI, 2022)
A large proportion of the rural population in Ethiopia depends on community-managed forests for food security and livelihoods. However, the government and development partners have paid little attention to the governance challenges which limit the contributions of community-managed forests to food security and livelihoods. Also lacking is a synthesis of evidence relating to the requirements for improved governance to support the efforts of decision makers and practitioners. This paper attempts to review and synthesize the available evidence with the aim of identifying the requirements to achieve improved governance in community-managed forests. The results revealed that failure to devise benefit-sharing mechanisms which consider the heterogeneity of rural communities was prevalent. Interference of local authorities and elite capture in decision-making processes of forest and landscape restoration also compromised the willingness of rural communities to engage in collective action. Requirements such as the identification of the needs of specific categories of communities and enabling of the negotiation of diverse interests in the design and implementation of interventions could improve the governance of community-managed forests. Developing management plans and business model scenarios which balance the ecological and socio-economic goals at a local level in collaboration with rural communities is important to improve the governance of community-managed forests. There is also a need to revisit the practice of evaluating the performance of community-managed forests almost exclusively based on the goals of climate change adaptation and mitigation and biodiversity conservation.